2016
DOI: 10.1007/s00167-016-4229-4
|View full text |Cite
|
Sign up to set email alerts
|

Anatomic single-bundle anterior cruciate ligament reconstruction improves walking economy: hamstrings tendon versus patellar tendon grafts

Abstract: II.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 47 publications
(66 reference statements)
1
6
0
1
Order By: Relevance
“…Valgus rotation (32,34), our results also showed that anatomical ACLR can restore knee kinematics during level walking. However, as was demonstrated by Figure 9, the non-anatomical ACLR in our study can also restore knee kinematics during level walking.…”
Section: Distal Translationsupporting
confidence: 70%
See 1 more Smart Citation
“…Valgus rotation (32,34), our results also showed that anatomical ACLR can restore knee kinematics during level walking. However, as was demonstrated by Figure 9, the non-anatomical ACLR in our study can also restore knee kinematics during level walking.…”
Section: Distal Translationsupporting
confidence: 70%
“…They found that the ACLR knees can maintain tibial rotational stability. Iliopoulos et al (32) summarized that nearly normalized locomotion economy was observed in anatomical ACLR with either hamstrings tendon or bone-patellar tendonbone graft during flat, uphill, and downhill walking. Akpinar et al (34) concluded no significant difference of knee kinematics was observed between anatomic ACLR knees and native knees at 24-month follow-up during downhill running.…”
Section: Discussionmentioning
confidence: 99%
“…Revisão da Literatura Iliopoulos et al (2017), compararam a eficácia da reconstrução anatômica do LCA com enxertos de tendões dos isquiotibiais (HAM) e osso -tendão patelar -osso (BPTB) na melhora e normalização do custo energético e reservas fisiológicas durante caminhadas planas, subidas e descidas. Para tanto, 20 indivíduos do sexo masculino com lesão unilateral do LCA foram aleatoriamente designados para reconstrução do LCA com enxerto HAM (n = 10) ou BPTB (n = 10).…”
Section: Resultsunclassified
“…Sufficient biomechanical strength and better clinical results concerning these grafts have been reported. 3,8,48,54,68,92,96 In addition, the quadriceps autograft is another choice of autograft. 3,36 It has been reported that the quadriceps autograft has the same level of strength with similarly good clinical results and without severe complications.…”
Section: Discussionmentioning
confidence: 99%